1965
DOI: 10.1128/jb.90.5.1355-1364.1965
|View full text |Cite
|
Sign up to set email alerts
|

Autolytic Mechanism for Spheroplast Formation in Bacillus cereus and Escherichia coli

Abstract: mechanism for spheroplast formation in Bacillus cereus and Escherichia coli. J. Bacteriol. 90:1355-1364. 1965.-Spheroplasts of Bacillus cereus strain T and Escherichia coli B were prepared by incubating early log-phase cells in appropriate buffers and stabilizers for 3 hr at 30 and 37 C, respectively. Upon incubation in 0.05 M tris(hydroxymethyl)aminomethane buffer osmotically stabilized with 16% polyethylene glycol at pH 7.5, 99% of the B. cereus cells formed spheroplasts; 90% of the E. coli cells were conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
11
0

Year Published

1967
1967
1980
1980

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 19 publications
6
11
0
Order By: Relevance
“…In sucroseinduced autolysis, the clostridial cells were converted into protoplasts through the morphological changes beginning both at the middle and one pole. The other morphological changes corresponded well with each case of lysis of E. coli (3,8,13). We will report the role of autolysin and sucrose in the morphological changes of the clostridial cells which occur during sucrose-induced autolysis in our next paper.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In sucroseinduced autolysis, the clostridial cells were converted into protoplasts through the morphological changes beginning both at the middle and one pole. The other morphological changes corresponded well with each case of lysis of E. coli (3,8,13). We will report the role of autolysin and sucrose in the morphological changes of the clostridial cells which occur during sucrose-induced autolysis in our next paper.…”
Section: Discussionsupporting
confidence: 64%
“…Cells of E. coli treated penicillin were converted into the spheroplasts through the morphological change beginning only at the middle (8). On the other hand, the cells autolysed in buffer were converted into the spheroplasts through the morphological change beginning only at one pole (13). In sucroseinduced autolysis, the clostridial cells were converted into protoplasts through the morphological changes beginning both at the middle and one pole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been suggested that increased osmotic pressure activates auto-lysis in Staphylococcus aureus (9). I t is also of interest that most active autolysis in intact bacteria has usually been observed after washing of the cells in distilled water (4, 9,10). As found in other systems (9, l o ) , maximal autolytic activity in N .…”
Section: Discussionmentioning
confidence: 98%
“…The cellular autolysis of bacteria is a phenomenon attributable to the hydrolytic degradation of cell wall peptidoglycans by their own enzyme(s). Studies by light and electron microscopy on Bacillus cereus and Escherichia coli (9), Clostridium botulinum (6), Clostridium perfringens (5), Streptococcus faecalis (3,4), group H streptococci strains Wicky and Challis (13), and Lactobacillus acidophilus (2) have revealed that cytoplasmic materials leak outward at the septal region by the autolysis, and that the autolysis was initiated at the septal site of dividing cells and at one pole of just separated cells, where cell wall materials were synthesized actively. In particular, Higgins et al (3) demonstrated by electron microscopy of thin sections that the initiation of cellular autolysis in dividing cells of S. faecalis was brought about by the dissolution of cell wall at the leading edge of nascent cross wall.…”
mentioning
confidence: 99%